2015
DOI: 10.1166/jbn.2015.2099
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Testing of Novel CARP-1 Functional Mimetic Compounds as Inhibitors of Non-Small Cell Lung and Triple Negative Breast Cancers

Abstract: The triple negative breast cancer (TNBCs) and non-small cell lung cancers (NSCLCs) often acquire mutations that contribute to failure of drugs in clinic and poor prognosis, thus presenting an urgent need to develop new and improved therapeutic modalities. Here we report that CARP-1 functional mimetic (CFMs) compounds 4 and 5, and 4.6, a structurally related analog of CFM-4, are potent inhibitors of TNBC and NSCLC cells in vitro. Cell growth suppression by CFM-4 and -4.6 involved interaction and elevated expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(73 citation statements)
references
References 40 publications
7
66
0
Order By: Relevance
“…Consistent with our previous observations with HBC cells, CFM-4 and CFM-5 compounds inhibited the growth of MPM, MB, NB, and NSCLC cells [6871] in part by activating apoptosis signaling and diminishing the levels of key cell cycle regulatory proteins including cyclin-B1, c- and N-myc. Both CFM-4 and CFM-5 compounds enhanced expression of CARP-1/CCAR1 along with activation of pro-apoptotic SAPKs (p38α/β and JNK1/2) [6871].…”
Section: Introductionsupporting
confidence: 91%
“…Consistent with our previous observations with HBC cells, CFM-4 and CFM-5 compounds inhibited the growth of MPM, MB, NB, and NSCLC cells [6871] in part by activating apoptosis signaling and diminishing the levels of key cell cycle regulatory proteins including cyclin-B1, c- and N-myc. Both CFM-4 and CFM-5 compounds enhanced expression of CARP-1/CCAR1 along with activation of pro-apoptotic SAPKs (p38α/β and JNK1/2) [6871].…”
Section: Introductionsupporting
confidence: 91%
“…The DEDD and DEDD2 proteins activate apoptosis by (a) binding and activating caspases-8, -10, and promoting activated caspase-8 translocation to the nucleus [61], (b) binding with cytosolic caspase-3 and enhancing its cleavage [62], and (c) trans-locating to nucleus and activating caspase-6 [63]. Our group has recently found that CFMs induce DEDD2 in MDA-MB-468 triple negative breast cancer, Daoy medulloblastoma, HepG2 liver, and HeLa cervical cancer cells [32]. Since DEDD and DEDD2 may be important mediators for death receptors and that these proteins often translocate activated caspases either in the nucleus or in the cytoplasm, understanding PTHrP's role in DEDD/DEDD2-dependent regulation of caspase-3 and nuclear-cytoplasmic translocation of CARP-1 as well as PTHrP antagonism of CFM's action in osteoblast warrants extensive investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Similar to proliferating cells CFM-1 did not reduce the viability of differentiated MC-4 osteoblasts (data not shown). The ineffectiveness of CFM-1 in osteoblast viability may be explained by the fact that the chemical structure, identity of CFM-1, and its interaction with CARP-1 and anaphase promoting complex/Cyclosome (APC/C) E3 ligase are different and distinct from CFM-4 and CFM-5 and also dependent on cell types [30,32].…”
Section: Cfm-4 and -5 Decreased Mc-4 Osteoblast Cell Survival In A Timentioning
confidence: 99%
See 2 more Smart Citations